The effect of the media reporting of terrorist attacks on the Czech travel insurance market between 2011-2016 - Petra Budská (European Financial and Accounting Journal, 2018)
Media plays a significant part of our lives and it has the power to provide us with ideas and/or some perspective on the selected topics. Terrorist attacks cause fear which is spread by media. The fact is that during the biggest 'terrorist fever' in the Czech Republic between 2015-2016, the number of terrorist attacks was paradoxically declining, and vice versa. The presented paper answers the question of how large is the effect of the media reporting of terrorist attacks on the number of travellers abroad and when - after how many quarters - the travellers' reaction follows. Based on the quarterly data of the number of travellers abroad and the gross premium written we found out that the media reporting of terrorist attacks is a significant variable and the decline in the number of travellers in some years represents the 'loss of one quarter' of travellers. Using the panel data model, we found out that although the number of travellers abroad has declined, the gross premium written has increased. Higher growth as well as significance in terms of the gross premium written was recorded only for the sole specialist on travel insurance in the Czech Republic - the ERV European Insurance Company when compared with the travel insurance market as a whole.
Keywords: C23; C29; G22; M39; 650; Insurance Premium; Media; Panel Data Models; Terrorist Attacks